ANALISIS UNDANG-UNDANG PERLINDUNGAN TENAGA KERJA INDONESIA DI LUAR NEGERI - Probosiwi, Ratih (Jurnal Kawistara, 2015)
The number of problems of migrant workers has been bothering public conscience widely, ranging from cases of deportation, persecution, rape, and even death threats to the workers. The Government considered not doing its job in protecting the workers optimally especially in the diplomatic process. The workers do not have bargaining positionsteadilythat weaken them so that arose the case and issues of migrant workers abroad. UU PPTKILN which has been legalized since 2004 was less able to base the protection of migrant workers abroad. This encourages the study of policy analysis to the migrant workers protection and result the idea that the law (UU PPTKILN) should be revised accordance with the Convention on Migrant Workers and regulate the rights and obligations of migrant workers in a comprehensive manner and uphold the dignity of workers. The government firmness needed to regulate and solve these problems not only inside but also outside (the destination countries of migrant workers).